2014
DOI: 10.1002/stem.1824
|View full text |Cite
|
Sign up to set email alerts
|

Daylight Vision Repair by Cell Transplantation

Abstract: Human daylight vision depends on cone photoreceptors and their degeneration results in visual impairment and blindness as observed in several eye diseases including age-related macular degeneration, cone-rod dystrophies, or late stage retinitis pigmentosa, with no cure available. Preclinical cell replacement approaches in mouse retina have been focusing on rod dystrophies, due to the availability of sufficient donor material from the rod-dominated mouse retina, leaving the development of treatment options for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
102
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 51 publications
10
102
1
3
Order By: Relevance
“…Despite heterogeneous expression of GFP throughout more than one cell population (cones and rod bipolars), GFP-positive cones are solely labeled until P14, allowing their enrichment using FACS. Transplantation of E17.5 Ccdc136 GFP/+ sorted cell fractions resulted in integrated photoreceptors in C57BL/6j wild-type hosts but these cells lacked the expression of cone-specific photo-transduction markers (Smiley et al, 2016) in contrast to Santos-Ferreira et al (2015) who showed cone markers (cone arrestin, s-opsin) in reporter labeled cells following cone-like photoreceptor transplantation into CPFL1 hosts. Interestingly, in both studies the reporter labeled cells within the host ONL frequently exhibited rod-like morphologies, that might be explained by the exchange of cell material between donor and host photoreceptors (see below).…”
Section: Transplantation Of Cone/cone-like Photoreceptorsmentioning
confidence: 92%
See 1 more Smart Citation
“…Despite heterogeneous expression of GFP throughout more than one cell population (cones and rod bipolars), GFP-positive cones are solely labeled until P14, allowing their enrichment using FACS. Transplantation of E17.5 Ccdc136 GFP/+ sorted cell fractions resulted in integrated photoreceptors in C57BL/6j wild-type hosts but these cells lacked the expression of cone-specific photo-transduction markers (Smiley et al, 2016) in contrast to Santos-Ferreira et al (2015) who showed cone markers (cone arrestin, s-opsin) in reporter labeled cells following cone-like photoreceptor transplantation into CPFL1 hosts. Interestingly, in both studies the reporter labeled cells within the host ONL frequently exhibited rod-like morphologies, that might be explained by the exchange of cell material between donor and host photoreceptors (see below).…”
Section: Transplantation Of Cone/cone-like Photoreceptorsmentioning
confidence: 92%
“…Functional analysis was performed by micro-electrode arrays (MEA), that allow the simultaneous read out of hundreds of retinal ganglion cells (RGCs). These measurements showed spike train responses in RGCs under daylight conditions (Santos-Ferreira et al, 2015). Importantly, sham or rod photoreceptor injected CPFL1 hosts were unable to detect high-intensity light stimuli.…”
Section: Transplantation Of Cone/cone-like Photoreceptorsmentioning
confidence: 95%
“…After dissection of the eyes, the retina was isolated and transferred to a papain solution (Worthington, Lakewood, USA) and incubated for 35 min at 37 °C 38 . Retinas dissociated to a single cell suspension were centrifuged for 5 min at 300 rcf, re-suspended in Fluorescence-activated cell sorting buffer (2 mM EDTA and 1% bovine serum albumin in PBS) and passed through a 40  μ m nylon cell strainer (BD Biosciences, Heidelberg, Germany) before FAC-sorting.…”
Section: Methodsmentioning
confidence: 99%
“…7,[25][26][27][28] Photoreceptor precursors at specific ontogenic stages (P4-P6) integrated into recipient adult retinas. 7,27) We theorized that if ES cells could differentiate into photoreceptors that correspond to the P4-P6 stages, those cells might integrate into the host retina and restore visual function.…”
Section: Retinal Regeneration: Past Present and Futurementioning
confidence: 99%